Advances in experimental social psychology. Volume 41 - Brinol, pablo; Zanna, Mark P.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier ; London ; Burlington, MA : Academic Press, 2009)
Containing contributions of empirical and theoretical interest, this title presents the best research, theory, and practice in social psychology.
Chapter 1 The Introspection Illusion / Emily Pronin -- Chapter 2 Persuasion: Insights from the Self-Validation Hypothesis / Pablo Briñol, Richard E. Petty -- Chapter 3 Action-Based Model of Dissonance: A Review, Integration, and Expansion of Conceptions of Cognitive Conflict / Eddie Harmon-Jones, David M. Amodio, Cindy Harmon-Jones -- Chapter 4 Affect as a Psychological Primitive / Lisa Feldman Barrett, Eliza Bliss-Moreau -- Chapter 5 Human Mimicry / Tanya L. Chartrand, Rick van Baaren -- Chapter 6 Ostracism: A Temporal Need-Threat Model / Kipling D. Williams.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Social psychology; Social psychology; Electronic books